THE INFLUENCE OF PRICE AND QUALITY OF DELIVERY SERVICES ON CONSUMER SATISFACTION LION PARCEL AGENT PT SWABINA GATRA TRAVEL - syamsul Arifin; Abdul Hamid; Nur Aini Anisa; Kurniawati -; Komarun Zaman; Etty Widawati; Mahmud Ismail (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This study was aimed to identify the effect of price and service quality of customer satisfaction Lion Parcel Agen PT Swabina Gatra Travel. This type of research is descriptive research with a quantitative approach. In which the sample of study consisted of 110 respondents. The data collection technique used a questionnaire distributed via google form. The results of this study indicate that the quality of service and product has a positive influence on customer satisfaction. This is reinforced by the value of the T-test of service and product quality variables whose significance value is below 0.05. The f test value also shows a sig value below 0.05, the coefficient of determination gets a value of 0.517, which means that the service quality and product quality variables affect the consumer satisfaction variable by 51.7 percent.